Role of argon plasma coagulation in management of bleeding GI tumors: evaluating outcomes and survival - Thosani, Nirav; Rao, Bhavana; Ghouri, Yezaz; Batra, Sachin; Raju, Gottumukkala; Shafi, Mehnaz; Guha, Sushovan (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Tumor related gastrointestinal (GI) bleeding is a challenging clinical problem in cancer patients. Argon plasma coagulation (APC) is preferred for the management of bleeding arterio-venous malformations. Our objective was to assess the role of APC in the management of bleeding GI tumors. Materials and Methods: This is a retrospective review of endoscopies performed at the UT MD Anderson Cancer Center over 3 consecutive years (2009-2011). This study involved patients with primary or metastatic gastrointestinal cancer with suspected GI bleeding and interventions included were endoscopies with APC. Our main outcome measurements were immediate hemostasis rate, change in transfusion requirements, re-bleeding rate, and 30-day mortality. Results: Immediate hemostasis was achieved in all 10 (100%) patients, with either APC performed alone (8 patients) or with adjuvant epinephrine (2 patients). There were no procedure related complications. The pooled transfusion requirements for all 10 patients 48 hours prior to the procedure were 26 packed red blood cells units, 11 platelet units and 6 fresh frozen plasma units, while the overall requirements in the 48 hours after the procedure were 5 packed red blood cells units, 6 platelet units and no fresh frozen plasma units. Re-bleeding occurred in 3 (30%) patients during follow up. Thirty day mortality rate was 0%. Total of 7 (70%) of patients were able to continue cancer specific therapy of either chemotherapy, radiation or both. Conclusion: APC is feasible and safe in routine practice to manage bleeding GI tumors. It is very effective in achieving initial hemostasis (100%) and allows majority of the patients (70%) to undergo cancer specific therapy.